Effects of anticonvulsants and inactivity on bone disease in epileptics. Issue 591 (January 1975) - Murchison, Lilian E.; Bewsher, P. D.; Chesters, Marion; Gilbert, J.; Catto, G.; Law, Elizabeth; McKay, E.; Ross, H. S.
Abstract : No significant biochemical or radiological features of vitamin D deficiency were found in groups of juvenile and adult epileptics and control groups of non-epileptic patients in hospitals for the mentally retarded. There was evidence of hepatic enzyme induction in patients on anticonvulsants, in that urinary D-glucaric acid concentration and excretion were raised. No effect was found of prolonged anticonvulsant therapy on bone densitometry, but in children immobility was closely associated with decreased bone density. The evidence suggests that disuse osteoporosis is the major bone disease in these mentally retarded children.